PERANCANGAN SISTEM INFORMASI PEMBAYARAN SPP DI SD MASEHI 3 KABANJAHE BERBASIS WEB - Nduru, Yiska Sonia Kristin; Siringoringo, Rimbun; Nainggolan, Rena (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The development of information technology has had a significant impact on managing data and information in the field of education. This study aims to design and develop a web-based tuition payment information system at SD Masehi 3 Kabanjahe to improve student data management and payment transactions. This information system is intended to assist teachers, administrative staff, and students in carrying out their duties more efficiently. The data collection method was carried out through observation and interviews with the school, as well as secondary data collection from existing documents. Based on the results of data analysis, this research resulted in the design of an information system that includes a web interface design for managing student data, information on tuition payments, and introducing the school to the public. The results of research on designing a web-based SPP payment information system that can assist users in recording, managing, and tracking SPP payments more efficiently. This system can also provide accurate and relevant information for parties involved in the educational process at SD Masehi 3 Kabanjahe. With this system, it is hoped that school administration management can be carried out more easily and effectively, and students can access tuition payment information quickly and comfortably.